Outcome Analysis of VP Shunt Surgery in post traumatic Hydrocephalus after Decompressive Craniectomy - Galav, Anshul Male (Nepal Journal of Neuroscience, 2025)
Introduction: Post traumatic hydrocephalus is one of significant complication post DC.PTH has significant morbidity and mortality. In this study we study prognostic and etiologic factors of PTH with outcome analysis. Materials and Methods: This prospective study includes 103 patients who underwent DC after TBI between august 22 and November 22 2022 at UPUMS Saifai Hospital and were still alive at 6-month follow-up. It was prospective cohort study. Various etiological factors and demographic factors correlated with outcome. Results: In this study total 103 patients studied among them 21 devloped PTH who undergone vp shunt. Low Glasgow Coma Scale (GCS) score, post DC meningitis, and intraventricular hemorrhage (IVH)and SAH were significant predictors for the development of PTH after DC. PTH patients showed impeded recovery or low-pressure hydrocephalus symptoms, of whom 9 experienced subjective clinical improvement after shunt treatment. TWO DC patients received a shunt due to subdural hygromas of whom one improved following treatment. Four patients were vegetative with concurrent ventriculomegaly and these patients did not have any positive shunt response. Altogether, 11 PTH patients improved after shunt surgery. Conclusion: Post-traumatic ventriculomegaly was common, but few developed symptomatic PTH and received a VP-shunt. Patients with low-pressure hydrocephalus symptoms had the best shunt response, whereas patients with suspected vegetative state exhibited a minimal shunt response.